2018
DOI: 10.1093/infdis/jiy495
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Translocation Does Not Drive Immune Activation in Ugandan Children Infected With HIV

Abstract: ObjectiveImmune activation is associated with morbidity and mortality during human immunodeficiency virus (HIV) infection, despite receipt of antiretroviral therapy (ART). We investigated whether microbial translocation drives immune activation in HIV-infected Ugandan children.MethodsNineteen markers of immune activation and inflammation were measured over 96 weeks in HIV-infected Ugandan children in the CHAPAS-3 Trial and HIV-uninfected age-matched controls. Microbial translocation was assessed using molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…We did not assess systemic drug concentrations of both ART and CPT in this study. While microbial translocation was shown to increase immune activation in cross-sectional studies in HIV-infected patients from the United States [ 11 ], studies in African populations did not show such association [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess systemic drug concentrations of both ART and CPT in this study. While microbial translocation was shown to increase immune activation in cross-sectional studies in HIV-infected patients from the United States [ 11 ], studies in African populations did not show such association [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study on a cohort of perinatally HIV-infected children [137] showed that ART initiation normalized sCD163 (marker of monocyte activation) levels and improved long-term pediatric outcomes. A recent study [138] agreed that immune activation decreases over time in children after starting ART, which does not have adverse effects itself on microbial translocation.…”
Section: Chronic Immune Activation and Persistent Inflammationmentioning
confidence: 95%
“…Measurement of microbial translocation plasma markers have been frequently performed in studies evaluating therapeutic interventions and assessing the risk of developing non-AIDS co-morbidities [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Circulating levels of lipopolysaccharide (LPS) are commonly measured to assess the level of bacterial translocation.…”
Section: Introductionmentioning
confidence: 99%